Kemajuan Teknologi Dalam Pengembangan Kompetensi Technopreneurship Muda Lokal Kota Semarang - Alfarizi, Muhammad; Ngatindriatun, Ngatindriatun (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2024)
Indonesia is entering the era of the fourth industrial revolution (4IR) with accelerated technology post-COVID-19 pandemic, supporting economic growth. Technopreneurship, a combination of high technology and entrepreneurship, plays a crucial role in developing a knowledge-based economy. The youth of Semarang, actively engaged in various fields, are expected to become successful technopreneurs with the support of education and training. This study aims to explore the influence of digital technology capabilities and technopreneurship knowledge on the technopreneurship competence of Semarang's youth. A quantitative approach was chosen, surveying 173 respondents from Semarang aged 18-35 years. Data were analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The hypothesis testing results indicate that digital technology capabilities and technopreneurship knowledge have a significant positive effect on technopreneurship self-efficacy. The role of technopreneurship self-efficacy also has a significant positive impact on technopreneurship competence, showing that high self-confidence encourages individuals to take risks and develop new business ideas. With support in technology infrastructure and entrepreneurship education, it is expected that more successful technopreneurs will emerge in Semarang, contributing to economic growth and local competitiveness.